Database Konsumen dan Sop Penjualan sebagai Peluang Peningkatan UMKM Mie Pangsit Ahuat - Tarekar, Wendy Wihue; Christiarini, Renny (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to improve the operational performance of Ahuat Dumpling Noodle MSMEs through the implementation of a customer database and a structured sales Standard Operating Procedure (SOP). The implementation of this program showed positive results, such as increased customer satisfaction with product quality (76.9%) and service speed (74.4%). Most customers prefer to dine-in (74.4%), demonstrating the importance of a hands-on dining experience. The program also succeeded in improving service efficiency and product consistency, although there are still opportunities for improvement, such as order management and payment systems. With these results, Mie Pangsit Ahuat is expected to improve its competitiveness in the market through data-driven strategies and consistent service, as well as capitalize on opportunities for product innovation development and delivery services.